Substitusi rumput lapang dengan hay African Star Grass (Cynodon plectostachyus) terhadap produktivitas kelinci lokal jantan - Syifa Nurjannah; Ikhsan Kholiq; Tedi Akhdiat; Nilawati Widjaya (Politeknik Negeri Jember, 2021)
The purpose of this research was to determine field grass substitution by hay African Star Grass (Cynodon plectostachyus) on the productivity of local male rabbits with an age of 3 months old. The research was conducted in October-November 2020 in Central Pojok Village, Cikahuripan, Lembang, West Bandung Regency. The research method used a completely randomized design with five treatments which were P0: 80% field grass + 20% concentrate; P1: 60% field grass + 20% hay African Star Grass + 20% concentrate; P2: 40% field grass + 40% hay African Star Grass + 20% concentrate; P3: 20% field grass + 60% hay African Star Grass + 20% concentrate; P4: 80% African Star Grass hay + 20% concentrate, and each treatment was repeated five times so that the number of rabbits used were 25 heads. Data obtained were analyzed using SPSS software and Duncan's multiple range test. The results showed that the substitution of field grass by Afrikan Star Grass affected ration consumption (P<0.05) with an average of 150.79-185.78 grams/head/day, but did not affect body weight gain and feed conversion (P>0.05) with an average of 14.64-19.78 grams/head/day and 7.94-11.60, respectively. This study concluded that the provision of hay African Star Grass at the level of 20% showed more optimal results.